Central EP3 (E Prostanoid 3) Receptors Mediate Salt-Sensitive Hypertension and Immune Activation. Issue 6 (December 2019) - Xiao, Liang; Itani, Hana A.; do Carmo, Luciana Simao; Carver, Lucas S.; Breyer, Richard M.; Harrison, David G.
Abstract : We recently identified a pathway underlying immune activation in hypertension. Proteins oxidatively modified by reactive isoLG (isolevuglandin) accumulate in dendritic cells (DCs). PGE2 (Prostaglandin E2) has been implicated in the inflammation associated with hypertension. We hypothesized that PGE2 via its EP (E prostanoid) 3 receptor contributes to DC activation in hypertension. EP3 −/− mice and wild-type littermates were exposed to sequential hypertensive stimuli involving an initial 2-week exposure to the nitric oxide synthase inhibitor N ω -nitro-L-arginine methyl ester hydrochloride in drinking water, followed by a 2-week washout period, and a subsequent 4% high-salt diet for 3 weeks. In wild-type mice, this protocol increased systolic pressure from 123±2 to 148±8 mm Hg ( P <0.05). This was associated with marked renal inflammation and a striking accumulation of isoLG adducts in splenic DCs. However, the increases in blood pressure, renal T-cell infiltration, and DC isoLG formation were completely prevented in EP3 −/− mice. Similar protective effects were also observed in wild-type mice that received intracerebroventricular injection of a lentiviral vector encoding shRNA targeting the EP3 receptor. Further, in vitro experiments indicated that PGE2 also acts directly on DCs via its EP1 receptors to stimulate intracellular isoLG formation. Together, these findings provide new insight into how EP receptors in both the central nervous system and peripherally on DCs promote inflammation in salt-induced hypertension. Abstract : Supplemental Digital Content is available in the text.